Evaluation of the Effectiveness of Distance Self-Care Training on Self-efficacy and Quality of Life of Patients With Intestinal Ostomy - Sattar Baab; Mehrdad Azarbarzin; Maryam Moghimian (Iran University of Medical Sciences, 2022)
Background & Aims: Living with a temporary or permanent ostomy affects the quality of life (QoL) of people with an ostomy and requires increasing patients' self-efficacy to take care of themselves. Education is one way to improve individuals' QoL and self-care. Therefore, this study aimed to determine the effectiveness of distance self-care education on self-efficacy and QoL of patients with an intestinal ostomy in patients referred to Kermanshah hospitals in 2020-2021. Materials & Methods: In a quasi-experimental study before and after the process, 61 patients with intestinal ostomy referred to Imam Reza (AS), and Taleghani hospitals in Kermanshah province were selected from April to July 2021, using a simple sampling method. The samples first answered the self-efficacy questionnaires of ostomy patients and the quality of life of Weir and Sherborn. Then, the self-care program developed in the form of 8 45-minute group sessions was taught to patients by the researcher through discussion and conversation through a virtual network (WhatsApp), according to which they can use self-care at home, and two months after the end of the intervention. The mentioned questionnaires were distributed and completed among the patients again. Data were reported using SPSS software v. 20, and paired t-test and Wilcoxon tests were used for statistical analysis. Results: The Mean±SD of patients' QoL before the intervention was 34.05±16.53, reaching 49.63±21.59 after the intervention. Based on paired t-test, this difference was significant (P<0.001). There was a statistically significant difference between the mean of all aspects of patients' QoL except general health before and after the intervention (P<0.043). The Mean±SD of patients' self-efficacy before the intervention was 50.40±4.57 (51.18±5.03 after the intervention) and based on the paired t-test, this difference was significant (P=0.036). Conclusion: The findings of the present study, while confirming and supporting the research hypothesis, showed that distance self-care education in patients with an intestinal ostomy effectively affects their self-efficacy and QoL. Using this treatment plan as one of the simple, cheap, feasible, and effective non-pharmacological interventions can help promote self-efficacy and, consequently, the QoL of the patients with an intestinal ostomy.